An Express just arrived from General Washington : Camp at Cambridge, Oct. 24, 1775. Sir, The inclosed information being of the highest importance, I thought it proper to transmit it to you with all dispatch, I am Sir, your obedient servant, George Washington : On the service of the United Colonies. To the Hon. Nicholas Cooke, Esq ; dep. gov. of Rhode-Island, Providence - Washington, George, 1732-1799; Cooke, Nicholas, 1717-1782; Jones, Pearson; Greene, Nathanael, 1742-1786 (LLMC-digital (Series), 1775)
Two letters concerning the destruction of Falmouth, Me., and the British intention to burn seaport towns between Boston and Halifax. The first, from Pearson Jones, is dated Falmouth, Monday, 16th Oct. 1775. The other, signed Nathaniel Green [i.e. Nathanael Greene], is dated Octobet [sic] 24. 1775.